Grammar, Philosophy, and Logic - Silver, Bruce (Springer International Publishing, 2018)
This book argues that a basic grasp of philosophy and logic can produce written and spoken material that is both grammatically correct and powerful. The author analyses errors in grammar, word choice, phrasing and sentences that even the finest writers can fail to notice; concentrating on subtle missteps and errors that can make the difference between good and excellent prose. Each chapter addresses how common words and long-established grammatical rules are often misused or ignored altogether - including such common words as 'interesting', 'possible', and 'apparent'. By tackling language in this way, the author provides an illuminating and practical stylistic guide that will interest students and scholars of grammar and philosophy, as well as readers looking to improve their technical writing skills. Bruce Silver is Professor Emeritus in the Department of Philosophy at the University of South Florida, USA.